Protein phosphatase 2A associates with and regulates atypical PKC and the epithelial tight junction complex - Nunbhakdi-Craig, Viyada (The Rockefeller University Press, 2002)
Tight junctions (TJs) play a crucial role in the establishment of cell polarity and regulation of paracellular permeability in epithelia. Here, we show that upon calcium-induced junction biogenesis in Madin-Darby canine kidney cells, ABαC, a major protein phosphatase (PP)2A holoenzyme, is recruited to the apical membrane where it interacts with the TJ complex. Enhanced PP2A activity induces dephosphorylation of the TJ proteins, ZO-1, occludin, and claudin-1, and is associated with increased paracellular permeability. Expression of PP2A catalytic subunit severely prevents TJ assembly. Conversely, inhibition of PP2A by okadaic acid promotes the phosphorylation and recruitment of ZO-1, occludin, and claudin-1 to the TJ during junctional biogenesis. PP2A negatively regulates TJ assembly without appreciably affecting the organization of F-actin and E-cadherin. Significantly, inhibition of atypical PKC (aPKC) blocks the calcium- and serum-independent membrane redistribution of TJ proteins induced by okadaic acid. Indeed, PP2A associates with and critically regulates the activity and distribution of aPKC during TJ formation. Thus, we provide the first evidence for calcium-dependent targeting of PP2A in epithelial cells, we identify PP2A as the first serine/threonine phosphatase associated with the multiprotein TJ complex, and we unveil a novel role for PP2A in the regulation of epithelial aPKC and TJ assembly and function.